Prevalence of posttraumatic stress disorder in acute trauma patients. Issue 1 (March 2020) - Joseph, Noah M.; Benedick, Alex; Flanagan, Christopher D.; Breslin, Mary A.; Simpson, Megen; Ragone, Christina; Kalina, Mark; Hendrickson, Sarah B.; Vallier, Heather A.
Abstract: Objective: To determine the prevalence of positive screening for posttraumatic stress disorder (PTSD) amongst trauma patients. Design: Prospective, longitudinal study. Setting: Single urban US level 1 trauma center. Patients and methods: Four hundred fifty-two adult trauma patients were administered the PTSD checklist for DSM-V (PCL-5) survey upon posthospital outpatient clinic visit. This included 300 men (66%) and 152 women with mean age 43.8 years and mean Injury Severity Score (ISS) 11.3, with 83% having fractures of the pelvis and/or extremities. Medical and injury related variables were recorded. Multivariate logistic regression analysis was performed to identify factors predictive of screening positive for PTSD. Main outcome measurement: Prevalence and risk factors for screening positive for PTSD amongst the trauma patient population. Results: Twenty-six percent of trauma patients screened positive for PTSD after mean 86 days following injury. These patients were younger (35 vs 46 years old, P < 0.001) and more commonly African American (56% vs 43% Caucasian, P < 0.001). Pedestrians struck by motor vehicles (OR 4.70, P = 0.040) and victims of crime (OR 4.12, P = 0.013) were more likely to screen positive. Psychiatric history, injury severity (ISS), and injury type did not predict positive screening. Conclusion: One-in-four patients suffering traumatic injuries screened positive for PTSD suggesting the prevalence of PTSD among trauma patients far exceeds that of the general population. Predictive factors included victims of crime and pedestrians struck by motor vehicles. Screening measures are needed in orthopaedic trauma surgery clinics to refer these at-risk patients for proper evaluation and treatment. Level of evidence: Prognostic; Level II